Separate and Unequal: A Sample of Disparities in Five American Unincorporated Territories. (4th July 2021) - Roman-Basora, Manuel; Bland, James Travis
Abstract : Recent natural disasters affecting the five populated unincorporated territories of the U.S. (Puerto Rico; Guam; American Samoa; U.S. Virgin Islands; and Northern Mariana Islands) have shed light on the inequities they encounter vis-à-vis the states of the union and Washington DC. In 2017, Puerto Rico and the U.S. Virgin Islands were devastated by two hurricanes (Irma and Maria). In 2018, American Samoa, Guam and Northern Mariana Islands were impacted by a cyclone (Gita), typhoon (Mangkhut), and a super typhoon (Yutu). These natural disasters have increased the interest of scholars in American overseas possessions in the Atlantic and Pacific. A review of journal publications and newspaper articles shows that the inequities faced by these locations are rarely studied comprehensively, as a group instead of individually. This article will focus on three specific areas in which the federal government discriminates against the group (with an emphasis on Puerto Rico): political representation, emergency management and welfare assistance. A subfield of study within American public administration is recommended: Unincorporation Studies. The development of this subfield would contribute to a better understanding of the discrimination based on location that these territories encounter as an integral part of America's 21st Century Civil Rights Movement.